PENGARUH MODEL PEMBELAJARAN MAKE A MATCH TERHADAP HASIL BELAJAR IPA SISWA KELAS V SD (STUDI LITERATUR) - Mutiasya, Irma; Sunarti, Yustia; Dallion, Engga (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This study aims to examine the effect of using the make a match learning model on the science learning outcomes of fifth grade elementary school students. The method used is a literature study by analyzing a number of related research journals. Data were taken from national journals that discuss the application of the make a match model in science learning in grade V elementary school and its impact on student learning outcomes. Data analysis was conducted using coding and content analysis techniques. The results showed that the use of the make a match learning model had a positive influence on improving the science learning outcomes of fifth grade students. This is evidenced by the increase in the average value of students' science learning outcomes after the application of the make a match model compared to before its application. In addition, the make a match model is also able to increase students' activeness, motivation, and interest in learning in the science learning process. It can be concluded that the make a match model is an effective learning model to be applied in learning science in grade V elementary school to improve student learning outcomes.